Meningkatkan Hasil Belajar Muatan IPA Melalui Model Pembelajaran Inkuiri Terbimbing pada Siswa Kelas IV Sekolah Dasar - Marlina Marlina; Siti Mariam; Asni Deselia Khairunnisa (Musamus Journal of Primary Education, 2021)
This study aims to improve the learning outcomes of science content through the Guded Inquiry Learning model for fourth grade students of SDN Bakambat. This research was conducted for two cycles using the Kemmis and Mc. Taggart design. The data were collected using observation and test. The data analysis was used qualitative and quantitative data. Qualitative data, namely the results of observations of teacher and student activities, quantitative data, namely student test results. The results showed that the teacher's activity in the first cycle was 50%, and the second cycle was 90%. Student activity in the first cycle was 57% and increased in the second cycle to 80%. Student learning outcomes in the first cycle were 52% and increased in the second cycle to 84%. The results of this study indicate that the implementation of the guided inquiry learning model in teaching science content can improve student learning outcomes in science content.